Rapid tranquillisation: a global perspective. (2nd January 2018) - Nadkarni, Pallavi; Jayaram, Mahesh; Nadkarni, Shailesh; Rattehalli, Ranga; Adams, Clive E.
Abstract : Violence and aggression among patients suffering from mental health problems undoubtedly pose a challenge to healthcare professionals, families and carers. Aggressive behaviours affect all aspects of clinical care. The goal of professionals is to ensure safety while effectively managing behavioural emergencies. 'Rapid tranquillisation' implies prescribing pharmacological agents to manage these behaviours. This article highlights changing prescription trends. Appraisal of global guidelines suggests that factors other than scientific evidence dictate their evolution. High-quality randomised controlled trials are needed to develop a global guideline.